The Validity of the Session Rating of Perceived Exertion Method for Measuring Internal Training Load in Professional Classical Ballet Dancers - Shaw, Joseph W.; Springham, Matthew; Brown, Derrick D.; Mattiussi, Adam M.; Pedlar, Charles R.; Tallent, Jamie (Frontiers in Physiology, 2020)
The aim of this study was to investigate the convergent validity of session rating of perceived exertion (s-RPE) with objective measures of internal training load in professional classical ballet dancers. Heart rate and s-RPE data were collected in 22 professional classical ballet dancers across a total of 218 ballet class or rehearsal sessions. Eleven participants completed at least 9 sessions, and were therefore included in analyses of individual relationships between s-RPE and objective measures. To calculate s-RPE, the session duration was multiplied by the rating of perceived exertion, measured using the modified Borg CR-10 scale. The Edwards summated heart rate zones (Edwards TRIMP) and Banister training impulse (Banister TRIMP) methods were used as criterion measures of internal training load. Pearson product-moment correlation coefficients were used to determine intra-individual relationships between s-RPE and objective measures. Repeated measures correlations were used to identify intra-individual relationships common across the cohort. Positive linear relationships were seen between s-RPE and objective measures across all session types (Edwards TRIMP: rrm (195) = 0.81, p < 0.001; Banister TRIMP: rrm (195) = 0.79, p < 0.001), in ballet class (Edwards TRIMP: rrm (58) = 0.64, p < 0.001; Banister TRIMP: rrm (58) = 0.59, p < 0.001), and in rehearsals (Edwards TRIMP: rrm (119) = 0.82, p < 0.001; Banister TRIMP: rrm (119) = 0.80, p < 0.001), as well as across both males (Edwards TRIMP: rrm (136) = 0.82, p < 0.001; Banister TRIMP: rrm (136) = 0.80, p < 0.001) and females (Edwards TRIMP: rrm (57) = 0.80, p < 0.001; Banister TRIMP: rrm (57) = 0.78, p < 0.001). Intra-individual correlation coefficients ranged from 0.46 – 0.96 (Edwards TRIMP: mean r = 0.81 ± 0.11, p = 0.051 – < 0.001; Banister TRIMP: mean r = 0.78 ± 0.14, p = 0.13 – < 0.001). These results demonstrate that s-RPE is a valid and practical method for measuring internal training load in professional classical ballet dancers.